Pengaruh Abu Cangkang Sawit Terhadap Kuat Tekan Dan Kuat Lentur Batubata - Herman .; Rolly I (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2018)
This research was conducted to increase the value of compreive strength by adding palm shell ash to the base soil of brick. The palm oil shell was got from the result of the disposal of Incasari Raya Factory Damasraya. The soil as the basic material of the brick was got from the brick’s manufactory Gunung Sariak Padang. The persentage of palm shell ash in the soil mixture was 0%, 5%, 15% and 25% from the soil dry weight. The test consisted of physical properties test and mechanical properties test. The physical properties test consisted of water content test, spesific gravity test, Atterberg limit test, and grain size analysis test.The mechanical properties test consisted of compaction test, compressive strength test and flexural strength test. The water content in manufacture brick was 0,85% γd maximum on wet side optimum of the soi. All the process of the brick is manufactured with manual fabrication. The result of the test showed that the values of spesific gravity (Gs), plastic limit (PL), shrinkage limit (SL),maximum dry density, optimum of water content, and compressive strength of brick increased. Mean while the liquid limit (LL),passing of sieve no. 200 in three days care, plastic index (PI), decreased. For flexural strength, at first increased, along with addition percentage from palm shell ash, this value inclined decreased. The optimum result was got 5% palm shell ash in the soil mixture.